Pengaruh People, Process, Physical Evidence Dan Promotion Terhadap Keputusan Siswa Memilih Kompetensi Keahlian - Wijaya, Ikhsan; Tasri, Evi Susanti (CV. ITTC INDONESIA, 2021)
The basis of the author's consideration of conducting research on the influence of people, process, promotion, and physical evidence on students' decisions to choose a skill program at SMKN 1 Lubuk Attitude is because they see the attractiveness of each skill competency which is increasingly diverse and so that each skill competency will certainly choose marketing strategy in competition to attract students as well as the efforts of each competency in maintaining and increasing student acceptance. The ultimate goal in this study is to test theories, build facts, show relationships and effects as well as comparisons between variables, provide statistical descriptions, interpret and predict the results. The population of this study was students of SMK Negeri 1 Lubuk Attitude in class X in the Odd semester of the 2021/2022 academic year, amounting to 492 people with a minimum sample of 100 people. Data processing using SEM-PLS. In this study it was found that People, Process, Physical evidence and Promotion had a positive and significant influence on the decision to select expertise competencies at SMKN 1 Lubuk Attitude. quality in the future, it is recommended that more efforts are made to improve the quality of people, process, physical evidence and promotion, because the results of this study have proven that people, process, physical evidence and promotion variables are important variables that influence student decisions in choosing skill competencies. at SMK Negeri 1 Lubuksikaping